Topological Phase Transition and Phase Diagrams in a Two‐Leg Kitaev Ladder System. Issue 4 (16th February 2020) - Yan, Yu; Qi, Lu; Wang, Dong‐Yang; Xing, Yan; Wang, Hong‐Fu; Zhang, Shou
Abstract: A scheme to investigate the topological properties in a two‐leg Kitaev ladder system composed of two Kitaev chains is proposed. In the case of two identical Kitaev chains, it is found that the interchain hopping amplitude plays a significant role in the separation of the energy spectrum and in inducing a topologically nontrivial phase, while the interchain pairing strength only affects the size of the energy gap. Moreover, another situation that the system consists of two non‐identical Kitaev chains is also investigated and the corresponding phase diagram is calculated. It is found that two pairs of degenerate nonzero edge modes will, respectively, appear in the upper and lower energy gaps when the interchain hopping amplitude or the interchain pairing strength is large enough. Furthermore, it is pointed out that the winding number is quantitatively equivalent to half of the number of zero energy edge modes in our system. Abstract : In the case of two identical Kitaev chains, the interchain hopping amplitude induces a topologically nontrivial phase. Two pairs of nonzero edge modes appear when the interchain hopping amplitude or interchain pairing strength is large enough in another case of two non‐identical Kitaev chains. The winding number is equivalent to half of the number of zero energy edge modes.